A Classroom Intervention of Enhancing Namibian Preservice Science Teachers’ Conceptual Understanding of Properties of Waves Through Mnemonics - Tomas Shivolo (Journal of Research in Mathematics, Science, and Technology Education, 2024)
This quantitative classroom intervention study investigated the effectiveness of using mnemonics to enhance preservice teachers’ conceptual understanding of the topic of wave properties in physics. The study involved a sample of 30 final-year undergraduate preservice teachers enrolled in the Bachelor of Education Honours, Senior Primary with specializations in Natural Science and Health Education at Dorado Campus of The International University of Management in Namibia. The primary objective was to assess the impact of a targeted mnemonic-based instructional intervention on their ability to comprehend and apply key physics concepts related to wave properties. Initially, participants’ baseline understanding of these concepts was evaluated through pre-intervention assessments, which provided a measure of their existing knowledge. A structured mnemonic-based teaching intervention was then implemented over a specified period, designed to facilitate improved understanding of wave properties. Following the intervention, post-assessment evaluations were conducted to compare and measure changes in the participants’ conceptual understanding of the subject matter. This comparative analysis aimed to identify any significant improvements resulting from the mnemonic-based instruction. The findings indicated that there were notable improvements in the participants’ conceptual grasp of wave properties after the mnemonic-based intervention. Additionally, the study collected and analyzed participants’ feedback regarding the use of mnemonics, offering insights into their perceptions of the technique’s effectiveness as a pedagogical tool for learning complex scientific concepts. This research contributes to the broader field of physics concepts by providing evidence-based strategies to enhance the preparation of preservice teachers, particularly in physics education. Ultimately, the results of this study have the potential to inform and improve teaching practices, fostering more effective and engaging educational experiences in future science classrooms.